Direct transfer of tri- and di-fluoroethanol units enabled by radical activation of organosilicon reagents - Xiang Chen (Nature Portfolio, 2020)
Methods for direct incorporation of tri- and di-fluoroethanol units in molecules are relatively limited. Here, the authors report two organosilicon reagents which are applied to allylation, alkylation and alkenylation reactions as tri- and di-fluoroethanol transfer reagents.